Політичні погляди учасників та сучасників національно-визвольної революції 1648-1676 рр. (Zaporizhzhia Historical Review, 2021)
At first in these article we have opportunity to see political loors as participants and contemporaries on The National-Liberation Revolution in the middle of XVII century.